2015
DOI: 10.2116/analsci.31.1309
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 265 nm Femtosecond and 213 nm Nanosecond Laser Ablation Inductively Coupled Plasma Mass Spectrometry for Pb Isotope Ratio Measurements

Abstract: The analytical performance of 265 nm femtosecond laser ablation (fs-LA) and 213 nm nanosecond laser ablation (ns-LA) systems coupled with multi-collector inductively coupled plasma mass spectrometry (MC-ICPMS) for Pb isotope ratio measurements of solder were compared. Although the time-resolved signals of Pb measured by fs-LA-MC-ICPMS showed smoother signals compared to those obtained by ns-LA-MC-ICPMS, similar precisions on Pb isotope ratio measurements were obtained between them, even though their operating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 36 publications
(36 reference statements)
0
7
0
Order By: Relevance
“…An inductively coupled plasma mass spectrometry (ICPMS) has also been more and more involved in isotope ratio measurements, especially for heavy elements such as Fe, Cu, Mo, Cd, Cs, Nd, Hf, W, Tl, Pb, U, and so on. 2,[5][6][7][8][9][10][15][16][17][18][19][20][21][30][31][32][33][34] However, the subjects still remain with respect to the analysis of light elements such as H, C, N, and O as well as Si, S and Cl, that suffer from the huge background signals from H2O, air entrainment (N2, O2, CO2) and Ar plasma gas.…”
Section: Introductionmentioning
confidence: 99%
“…An inductively coupled plasma mass spectrometry (ICPMS) has also been more and more involved in isotope ratio measurements, especially for heavy elements such as Fe, Cu, Mo, Cd, Cs, Nd, Hf, W, Tl, Pb, U, and so on. 2,[5][6][7][8][9][10][15][16][17][18][19][20][21][30][31][32][33][34] However, the subjects still remain with respect to the analysis of light elements such as H, C, N, and O as well as Si, S and Cl, that suffer from the huge background signals from H2O, air entrainment (N2, O2, CO2) and Ar plasma gas.…”
Section: Introductionmentioning
confidence: 99%
“…Laserinduced downhole fractionation of 206 Pb and 238 U was detected during zircon dating using a 260 nm NWR fs-LA and attributed to thermal effects by Hattori et al (2017) 7 , although the observed fractionation was smaller than that induced during ns-LA. In addition, comparable elemental fractionation effects have been noted using 193 nm nanosecond-LA (ns-LA), 265 nm fs-LA and 795 nm fs-LA, 85,86 and elemental fractionation was observed on 66 Zn/ 65 Cu and 208 Pb/ 238 U ratios in the aerosol produced by fs-LA of silicate glass (SRM NIST 610) by Koch et al (2006). 87 Heat diffusion processes can penetrate a zone encompassing several hundreds of nm even using short pulse length fs-LA, 88 and the chemical composition of aerosols produced during the fs-LA of natural and synthetic solids is dependent on particle size and morphology as pronounced element partitioning into different particle size fractions has been observed.…”
Section: Ion Counter Correctionsmentioning
confidence: 85%
“…134 The internal and external reproducibility of isotope composition, element concentration and ratio depend primarily on instrument dri, matrix difference between reference materials and samples, signal stability and signal intensity. Typical uncertainties (2 s) are about 1%, 1-2% and 1-3% for 206 Pb/ 238 U ages measured with a MC-ICP-MS, sector eld ICP-MS and single quadrupole ICP-MS, respectively, 12,13,17,132,135 0.007-0.01% for 176 Hf/ 177 Hf, [12][13][14]17 0.01% for 143 Nd/ 144 Nd 16,133 and 0.015% for 86 Sr/ 87 Sr. 16 However, the main limitation of simultaneous measurement of multiple isotope systems is that the signal intensity on the individual ICP-MS instruments decreases, compared to that obtained from separate measurements of Sr, Nd, Hf, and U-Pb isotopes and trace elements. Signal intensity can be improved if the He carrier gas is mixed with a small amount of N 2 (less than 5 mL min À1 ) before it enters the ICP.…”
Section: Laser Ablation Split Stream (Lass) Methodsmentioning
confidence: 99%
“…Ohata et al reported on "Comparison of 265 nm Femtosecond and 213 nm Nanosecond Laser Ablation Inductively Coupled Plasma Mass Spectrometry for Pb Isotope Ratio Measurements". 5 They revealed the similar analytical performance of 265 nm femtosecond laser and 213 nm nanosecond laser ablation systems for Pb isotope ratio measurements of solder. They also reported on "Studies on Isotope Ratio Measurement of Cl by Inductively Coupled Plasma Triple-quad Mass Spectrometry", describing an isotope ratio measurement of Cl using ICP-MS/ MS. 6 Similar sensitivities as those obtained by ICP-SFMS and the precisions of 0.2 -0.5% of RSD at the concentration range of 1 -10 mg kg -1 were obtained.…”
mentioning
confidence: 75%